Contribuições da literatura brasileira contemporânea ao “livro de registro da cidade” - Vera Lúcia Cardoso Medeiros (Estudos de Literatura Brasileira Contemporânea)
This article develops an analysis of the representation of the city in stories and novels by writer Clarice Lispector from different periods, trying to identify what the main issues highlighted by the author as well as the relationships established between the subject, the street and the city. In a second step, it is proposed reading of the same theme in the work Prosas cariocas, organized by Marcelo Moutinho and Flavio Izhaki and published in 2004, seeking to establish relationships with Lispector’s work and, thus, understand if, between the second half of the century twentieth and early twenty-first century, there were significant changes in representation that literature has made Brazilian city.